MENUJU LABORATORIUM ANALISIS LlNGKUNGAN TERPADU DAN TANTANGAN MASA DEPAN - Soefjan Tsauri; Soemanto Imamkhasani (Jurnal Kimia Terapan Indonesia, 2000)
An idea on an integrated environmental analytical laboratoryand its challenges for the future were discussed. A generalanalytical laboratory equipped with conventional and instrumentalmethods could be improved to environmental laboratory byaddition of sampler eguipment. These include water sampler, impinger for sampling of ambient air, stack gas sampler andleaching test (TCLP) , all of these have been made locally andtherefore easily purchased with low price. Laboratory accreditationwas also discussed for improving the quality of laboratory as areliable environmental data generator. Accreditation requirementssuch as registration, methods of analysis, quality control, physicalcondition of lab oratory, equipment and instrument were explained.In addition, other challenges in research were pointed out on thearea of semi-micro techniques, sensor, micro-instruments,automation and telemetric system. Experiences showed thatenvironmental analytical laboratory had good challenges forbusiness. Analytical services, development of monitoring systemand training were identified as prospective business in Indonesiaparticularly in East of Java.